Ready player one - Cline, Ernest (Ready Player One, 2011)
"It's the year 2044, and the real world is an ugly place. Like most of humanity, Wade Watts escapes his grim surroundings by spending his waking hours jacked into the OASIS--a sprawling virtual utopia that lets you be anything you want to be. Wade dreams of being the one to discover the ultimate lottery ticket that lies concealed within this virtual world. OASIS creator James Halliday has hidden a series of fiendish puzzles that will yield massive fortune--and remarkable power--to whoever can unlock them. ... And then, Wade stumbles upon the first puzzle."